Effectiveness of etanercept biosimilar SB4 in maintaining low disease activity in patients with psoriatic arthritis switched from etanercept originator: an open-label one year study. (2nd October 2020) - Bonifati, C.; De Felice, C.; Lora, V.; Morrone, A.; Graceffa, D.
Abstract: Background: Currently, there are no studies specifically aimed at investigating the effectiveness of etanercept biosimilar SB4 in psoriatic arthritis (PsA). Objectives: Our primary objective was to verify the ability of SB4 to maintain low disease activity in patients switching from reference etanercept to SB4 after 1 year of treatment with this last drug. Methods: Eighty-seven PsA patients with low disease activity at baseline measured by using the clinical Disease Activity Index for Psoriatic Arthritis ≤ 13 (cDAPSA; range 0–154) were prospectively evaluated after 6 and 12 months when switching from the reference etanercept to SB4. Results: One year after switching from the reference etanercept to SB4, 76 (87.3%) out of 87 patients maintained a cDAPSA ≤ 13. Conclusions: SB4 was effective in maintaining a state of low disease activity in the majority of patients switched from the reference etanercept. However, the proportion of patients (11 subjects) who failed to maintain a state of low disease activity at the end of the study was statistically significant. Loss of effectiveness in the above subjects was mainly due to subjective evaluations given by the patients, rather than an objectifiable exacerbation of disease.